21st Century Teaching Strategic Competencies to be Developed by ELT Instructors - Pachon Jaramillo, Alejandro (Coloquio, 2023)
This reflective article dives into the imperative need for ELT instructors to teach 21st-century skills. The study investigates various strategies to foster language learning through ICTs’ core elements integration within culturally responsive classrooms. Data were gathered through an extensive bibliographic analysis, encompassing papers, articles, and documents from diverse sources. The resultant findings underscored the vital need to incorporate ICTs and culture-based strategies by ELT instructors to propel students toward success in the dynamic horizon of 21st-century language acquisition.